2021
DOI: 10.52600/2763-583x.bjcr.2021.1.2.26-31
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Obstruction by Tricobezoar in Cat Associated with Lynxacarus radovskyi: a Case Report

Abstract: The presence of trichobezoar in cats is characterized by the accumulation of hair in the gastric cavity, which may be associated with the presence of dermatitis caused by the presence of the mite Lynxacarus radovskyi. In the present report, a clinical case of a feline patient with diagnostic and surgical diagnosis of the presence of a trichobezoar with the presence of Lynxacarus radovskyi in a skin scrape examination was described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Arruda et al reported a similar case in a domestic cat where the cat's skin was infested with mites. 16 However, in the case of the jungle cat, we were unable to identify the ectoparasites responsible for the skin lesions.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Arruda et al reported a similar case in a domestic cat where the cat's skin was infested with mites. 16 However, in the case of the jungle cat, we were unable to identify the ectoparasites responsible for the skin lesions.…”
Section: Discussionmentioning
confidence: 94%
“…so forth. 16 However, diagnosing this condition in wild cats becomes challenging without a detailed history and prominent clinical signs. This presents additional difficulties in treating rescued cats effectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations